Impact of COVID-19 restrictions on carers of persons with dementia in the UK: a qualitative study - Sriram, V; Jenkinson, C; Peters, M (Oxford University Press, 2021)
Background: Informal carers provide the majority of the support for persons with dementia living at home. Restrictions imposed due to COVID-19 have had a profound impact on the daily life of the entire population. This study provides insight into the impact of these restrictions on carers of people with dementia living at home.